The Role of Environmental Factors In Stunting In Rural Areas - Murwanto, Bambang; Santosa, Imam; Ginting, Daria Br; sutarto, sutarto (Universitas Aisyah Pringsewu, 2025)
Stunting, characterized by inadequate height-for-age, reflects chronic malnutrition in children and remains a critical public health issue, particularly in rural areas of low- and middle-income countries. This review investigates environmental factors influencing stunting, such as food availability, water quality, sanitation, and socioeconomic conditions. The analysis is based on systematic literature reviews of studies from 2010 to 2024, focusing on articles from databases like PubMed, Scopus, and Google Scholar. Findings highlight that poor food availability, characterized by limited access to nutritious food, contributes significantly to stunting. Poor water quality and inadequate sanitation lead to frequent intestinal infections, further exacerbating malnutrition and stunting. Socioeconomic factors, including low parental education and economic status, affect access to resources and health services. Data reveal that children from economically disadvantaged families and those with lower maternal education levels are at higher risk of stunting. Interventions such as improving water and sanitation infrastructure, enhancing parental education, and increasing economic opportunities are essential. Additionally, the media plays a role in raising awareness about nutrition. Strengthening community-based programs and improving infrastructure in rural areas can help address the stunting problem effectively. This review underscores the need for multifaceted strategies combining environmental and socioeconomic improvement to combat stunting.